Single-Cell RNA-Sequencing From Mouse Incisor Reveals Dental Epithelial Cell-Type Specific Genes - Chiba, Yuta; Saito, Kan; Martin, Daniel; Boger, Erich T.; Rhodes, Craig; Yoshizaki, Keigo; Nakamura, Takashi; Yamada, Aya; Morell, Robert J.; Yamada, Yoshihiko; Fukumoto, Satoshi (Frontiers in Cell and Developmental Biology, 2020)
Dental epithelial stem cells give rise to four types of dental epithelial cells: inner enamel epithelium (IEE), outer enamel epithelium (OEE), stratum intermedium (SI), and stellate reticulum (SR). IEE cells further differentiate into enamel-forming ameloblasts, which play distinct roles, and are essential for enamel formation. These are conventionally classified by their shape, although their transcriptome and biological roles are yet to be fully understood. Here, we aimed to use single-cell RNA sequencing to clarify the heterogeneity of dental epithelial cell types. Unbiased clustering of 6,260 single cells from incisors of postnatal day 7 mice classified them into two clusters of ameloblast, IEE/OEE, SI/SR, and two mesenchymal populations. Secretory-stage ameloblasts expressed Amel and Enam were divided into Dspp + and Ambn + ameloblasts. Pseudo-time analysis indicated Dspp + ameloblasts differentiate into Ambn + ameloblasts. Further, Dspp and Ambn could be stage-specific markers of ameloblasts. Gene ontology analysis of each cluster indicated potent roles of cell types: OEE in the regulation of tooth size and SR in the transport of nutrients. Subsequently, we identified novel dental epithelial cell marker genes, namely Pttg1, Atf3, Cldn10, and Krt15. The results not only provided a resource of transcriptome data in dental cells but also contributed to the molecular analyses of enamel formation.